(untitled) (International Research in Economics and Finance, 2022)
In the current civil and commercial cases involving disputes over the ownership of data, judges tend to use the Anti-unfair Competition Law to regulate and protect the property rights and interests of databases. However, due to the limited scope of adjustment, incomprehensive protection, and other defects of the Anti-unfair Competition Law, the Anti-unfair Competition Law is not sufficient to regulate database rights and interests. In response, the Western countries have adopted special Database Protection Directive which has been transformed into a special protection for databases. There is also a new model of protection under patent laws. In the era of the booming development of big data, the problem of database rights and interests protection urgently needs a more comprehensive legislative solution.